Influence of Concurrent Finger Movements on Transcranial Direct Current Stimulation (tDCS)-Induced Aftereffects - Shirota, Yuichiro; Terney, Daniella; Antal, Andrea; Paulus, Walter (Frontiers in Behavioral Neuroscience, 2017)
Transcranial direct current stimulation (tDCS) has been reported to have bidirectional influence on the amplitude of motor-evoked potentials (MEPs) in resting participants in a polarity-specific manner: anodal tDCS increased and cathodal tDCS decreased them. More recently, the effects of tDCS have been shown to depend on a number of additional factors. We investigated whether a small variety of movements involving target and non-target muscles could differentially modify the efficacy of tDCS. MEPs were elicited from the right first dorsal interosseous muscle, defined as the target muscle, by single pulse transcranial magnetic stimulation (TMS) over the primary motor cortex (M1). During M1 tDCS, which lasted for 10 min applying anodal, cathodal, or sham condition, the participants were instructed to squeeze a ball with their right hand (Task 1), to move their right index finger only in the medial (Task 2), in the lateral direction (Task 3), or in medial and lateral direction alternatively (Task 4). Anodal tDCS reduced MEP amplitudes measured in Task 1 and Task 2, but to a lesser extent in the latter. In Task 3, anodal tDCS led to greater MEP amplitudes than cathodal stimulation. Alternating movements resulted in no effect of tDCS on MEP amplitude (Task 4). The results are congruent with the current notion that the aftereffects of tDCS are highly variable relying on a number of factors including the type of movements executed during stimulation.